Virtualization as a viable alternative in educational institutions - Valero Palomino, Fiorella Rocío (2021)
This paper parts of the fact that the COVID-19 pandemic motivated the virtualization of education. On the face of it, an interest arose to know how this modality advanced in Latin American region. The objective of this article is to explore the references about the virtualization in educational institution and the analysis of them. It was used a qualitative approach with a phenomenological method and a technique of selected content. The results were that the virtualization of education is a progressive trend. Educational management in this modality requires new competencies in educational community. Also, there is evidence of adaptation to digital media at an acceptable level in some educational institutions. Therefore, a potential in virtual education was identified to drive the democratization of education due to its reach through mobile devices.